2015
DOI: 10.1007/s11356-015-4618-0
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical fractions and risk assessment of trace elements in soils around Jiaojia gold mine in Shandong Province, China

Abstract: Soils located adjacent to the Jiaojia gold mine were sampled and analyzed to determine the degree of which they were contaminated by trace elements (Hg, As, Cd, Pb, Cu, and Zn) in Shandong Province, China. All 18 samples exhibited mean Hg, As, Cd, and Pb concentrations in excess of local background values, while the mean concentrations of Cu and Zn were below the background values. In addition, the concentrations of trace elements in gold smelter (GS) soils were higher than in the gold mine (GM) soils. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 35 publications
(35 reference statements)
0
5
1
Order By: Relevance
“…Although toxicity of lead from industrial settings has been relatively controlled, it remains a pervasive toxicant worldwide (Arif et al, 2015;Azizi and Azizi, 2010). In comparison with other similar studies, the mean concentration of Pb in soil of study area was significantly higher than the concentrations reported in Sudan, Ghana and South Africa, respectively by Mushtaha et al (2017), Crentsil and Anthony (2016) and Caspah et al (2016), in addition, this concentration was also higher than obtained in the studies carried out by Feifei et al (2015) and Sijin et al (2015), respectively around a gold mine and Zinc-Lead mining area in China (Table 4). Concentrations of Arsenic (As) range from 0.0 to 16.2 ppm with a mean value of 4.6±4 ppm (Table 2) at Bétaré Oya and from 0.0 to 5.6 ppm with a mean value of 3±2.4 at Batouri (Table 3).…”
Section: Heavy Metals Concentrationscontrasting
confidence: 74%
See 2 more Smart Citations
“…Although toxicity of lead from industrial settings has been relatively controlled, it remains a pervasive toxicant worldwide (Arif et al, 2015;Azizi and Azizi, 2010). In comparison with other similar studies, the mean concentration of Pb in soil of study area was significantly higher than the concentrations reported in Sudan, Ghana and South Africa, respectively by Mushtaha et al (2017), Crentsil and Anthony (2016) and Caspah et al (2016), in addition, this concentration was also higher than obtained in the studies carried out by Feifei et al (2015) and Sijin et al (2015), respectively around a gold mine and Zinc-Lead mining area in China (Table 4). Concentrations of Arsenic (As) range from 0.0 to 16.2 ppm with a mean value of 4.6±4 ppm (Table 2) at Bétaré Oya and from 0.0 to 5.6 ppm with a mean value of 3±2.4 at Batouri (Table 3).…”
Section: Heavy Metals Concentrationscontrasting
confidence: 74%
“…When the quantities of Cu and Zn in the body increase they become toxic, which can result in damaged and malfunctioning human organs (USEPA, 2013;Bost et al, 2016;Fraga, 2005;Tobias et al, 2013). The level of Zn in this study area was higher than the concentrations found in studies on soils around gold mine in China (Feifei et al, 2015) and Sudan (Mushtaha et al, 2017) but lower than Zn concentration (112.3 ppm) reported in Zinc-Lead mining area in China (Sijin et al, 2015).…”
Section: Heavy Metals Concentrationsmentioning
confidence: 59%
See 1 more Smart Citation
“…Due to the above facts, soil environmental sampling has become a crucial means to evaluate the anthropogenic pollution with PTEs. Over the past few years, several studies to determine the contamination of PTEs in the soils of neighboring gold mines have been conducted in many countries [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The waste of ASGM was discharged to land without any treatment, which will pollute the surrounding soil. In China, it was found that the concentration of Hg in tailings was relatively higher than background concentrations [ 14 ]. Moreover, in Indonesia, ASGM activities in Central Java caused a great deal of Hg pollution to local streams [ 23 ].…”
Section: Introductionmentioning
confidence: 99%